2014
DOI: 10.1111/pace.12508
|View full text |Cite
|
Sign up to set email alerts
|

Lumenless Pacing Leads: Performance and Extraction in Pediatrics and Congenital Heart Disease

Abstract: During up to 6 years of use in pediatric and CHD patients, the M3830 lead has demonstrated excellent efficacy, a low rate of complications, and straightforward extractability relative to traditional pacing leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 11 publications
7
33
1
2
Order By: Relevance
“…). The 4.1‐Fr M3830 has demonstrated favorable acute and chronic performance with low complication rates . A more recent study by Garnreiter et al.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…). The 4.1‐Fr M3830 has demonstrated favorable acute and chronic performance with low complication rates . A more recent study by Garnreiter et al.…”
Section: Discussionsupporting
confidence: 73%
“…Previous reports have shown no differences in comparative lead sensing or pacing performances . Several studies have reported excellent short‐term as well as chronic lead performance (pacing/sensing) outcomes of the lumenless 4.1‐Fr diameter M3830 leads in pediatric and CHD populations . Unfortunately, there is limited comparative information on AVV integrity or vascular (SVC/innominate [INN]) dimensions between these lead designs and none in the young or those with CHD .…”
Section: Introductionmentioning
confidence: 99%
“…This may be the best way of extracting these leads, as most of the cutting sheaths are designed for bigger leads, and the mismatch in sheath/lead size may result in an increased risk of vessel perforation. Garnreiter et al 13 showed that these leads can be removed using manual traction alone, with the oldest lead in this cohort being 4 years. Nevertheless, in many cases a cutting sheath will still be required for extensively fibrosed leads having many adhesion points.…”
Section: Discussionmentioning
confidence: 95%
“…10 Data on lead extraction in pediatric and adult congenital heart disease (ACHD) patients are limited, particularly in relation to SelectSecure extractions. 2,12,13 An understanding of the outcomes associated with lead extraction, along with the nuances required for each type of lead, is essential to optimize our choice of pacing lead. 2,14 We report our tertiary center experience on extraction of SelectSecure leads compared to conventional (stylette-driven) pacing leads in a cohort of pediatric and ACHD patients.…”
Section: Introductionmentioning
confidence: 99%
“…SDS has been the only method for lead delivery for more than 20 years and is currently the standard technique for lead implantation. Currently, CDS is reported to be an important delivery system when performing His‐pacing and implanting leads in patients with congenital heart disease . In this study, we will compare SDS and CDS to test our hypothesis that the catheter‐based delivery system is a safer and significantly more efficient technique than SDS, as the specific catheter always points to the interventricular septum.…”
Section: Discussionmentioning
confidence: 99%